O! WHAT A NOBLE MIND IS HERE O'ERTHROWN!. (29th November 2012) - Adler, H; Mat, A; Merwick, A; Chadwick, G; Gullo, G; Dalmau, J; Tubridy, N
Abstract : Ophelia Syndrome is a rare paraneoplastic limbic encephalitis seen in the setting of Hodgkin's lymphoma (HL) that may present with progressive behavioural, memory or psychiatric disturbances. In most cases, initial physical examination, laboratory tests and imaging studies yield few abnormalities and the discovery of the causal neoplasm often lags behind these symptoms. A potential diagnostic tool has emerged for suspected cases in the form of anti-neuronal antibodies, and a recent publication described anti-mGluR5 antibody detection in the sera of two cases. We report a case of Ophelia Syndrome presenting with a prolonged period of behavioural (often violent) disturbances. A supraclavicular lymphadenopathy and unusual MRI abnormalities in the pons prompted a search for Hodgkin's lymphoma. Anti-mGluR5 antibody was subsequently detected in the CSF confirming the diagnosis of Ophelia Syndrome.